2020
DOI: 10.1186/s13046-020-01559-1
|View full text |Cite|
|
Sign up to set email alerts
|

A novel ETV6-miR-429-CRKL regulatory circuitry contributes to aggressiveness of hepatocellular carcinoma

Abstract: Background: Tumor metastasis is one of the main causes of the high mortality of hepatocellular carcinoma (HCC). E-Twenty Six variant gene 6 (ETV6) is a strong transcriptional repressor, associated with the development and progression of tumors. However, the exact role and underlying mechanism of ETV6 in HCC remain unclear. Methods: Western blotting, quantitative real-time PCR and immunohistochemistry were used to detect the expression levels of ETV6, CRKL (v-crk sarcoma virus CT10 oncogene homologue (avian)-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(45 citation statements)
references
References 53 publications
6
39
0
Order By: Relevance
“…Our previous work also indicated that CRKL upregulation potentially promoted HCC progression by enhancing the in vitro malignant behaviors of HepG2 cells ( Guo et al, 2018 ). The in vitro data on miR-124-3p and CRKL expression as well as invasion and migration activities in HCC cells from current study are consistent with our previous studies ( Guo et al, 2018 , 2020 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our previous work also indicated that CRKL upregulation potentially promoted HCC progression by enhancing the in vitro malignant behaviors of HepG2 cells ( Guo et al, 2018 ). The in vitro data on miR-124-3p and CRKL expression as well as invasion and migration activities in HCC cells from current study are consistent with our previous studies ( Guo et al, 2018 , 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…Twenty three frozen HCC human tissues including their corresponding non-tumor liver tissues (14 male and 9 female patients, 8 patients under ≥ 60 age and 15 < 60 age) were used for comparative miR-124-3p expression analysis. However, the CRKL protein expression analysis from these tissues was already reported in our previous work ( Guo et al, 2018 , 2020 ). In the current work, we quantified miR-124-3p in these tissues and correlated miR-124-3p expression from the current study, with CRKL expression from a previous study.…”
Section: Methodsmentioning
confidence: 81%
See 1 more Smart Citation
“…CRKL is a major tyrosine-phosphorylated protein in CML cells, pCRKL plays a special role in CML pathogenesis, and the constitutive phosphorylation of CRKL is unique to CML, which makes it a useful target for therapeutic intervention [42][43][44]. We previous reported that CRKL is associated with proliferation, migration and invasion of hepatocarcinoma and clear cell renal cell carcinoma cells [45][46][47][48][49][50]. However, the exact role of CRKL in CML is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…For IHC staining, the experiment was performed using manufacturer's instructions for kits SP-9001 (Zhong Shan-Golden Bridge Biological Technology). IHC assays were scored as previously describe [36].…”
Section: Immunocytochemical (Icc) and Immunohistochemical (Ihc) Stainingmentioning
confidence: 99%